Landscapes and Landforms of Namibia - Goudie, Andrew; Viles, Heather; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2015)
The landscapes of Namibia are of world-class quality in beauty, diversity and interest. This book provides the first ever overview of the most important of these landscapes, explains why they look as they do, and evaluates why they are of note. Writing from a geomorphological perspective, the authors introduce the key processes and controls which influence landscape and landform development in Namibia. Geological and tectonic background, climate now and in the past, vegetation and animals (including humans) are all identified as crucial factors influencing the landscape of Namibia today. The book presents twenty one richly-illustrated case studies of the most significant landscapes of Namibia, ranging from the iconic Etosha Pan at the heart of the biggest wildlife conservation area in the north, to the famous dunes and ephemeral river at Sossus Vlei in the heart of the Namib desert. Each case study also contains a full list of the key references to the scientific work on that landscape. The authors provide an assessment of the current state of conservation of these landscapes, and their importance to tourism. The book is recommended reading for anyone with a professional or amateur interest in the spectacular and intriguing landscapes of this part of southern Africa. It provides a useful handbook for those travelling around Namibia, and an invaluable reference guide for those interested in how landscapes develop and change.
From the Contents: Geological and tectonic background -- Climate past and present -- Long-term geomorphological history -- Geomorphological regions -- Brandberg -- Brukkaros Volcano -- Cunene River, the oshanas, bedrock channel and major falls -- Erongo Mountains: Ameib, Bulls Parties, Phillips Cave -- Etendeka Plateau and the Messum Crater -- Etosha Pan -- Gamsberg Plateau -- Giant$1 (Bs Playground dolerite complex -- Gobabeb and the Central Namib inselbergs and weathering phenomena -- Kolmanskop barchans -- Kuiseb Canyon, Gravel Plains, Calcretes and Gramadullas -- Naukluft Tufsa.s
Keywords: Geography; Physical geography; Geomorphology; Geoecology; Environmental geology; Geography; Geomorphology; Physical Geography; Geoecology/Natural Processes; Electronic books